LEARNING MANAGEMENT BASED ON INDIVIDUAL NEEDS ASSESSMENT IN CHILDREN WITH DISABILITIES - Hadi, Imam Anas (Tahta Media Group, 2025)
This study aims to analyze the implementation strategies of learning management based on individual needs assessment for students with disabilities at SMK Muhammadiyah Delanggu. The research employed a qualitative approach with a case study design. Data were collected through observation, in-depth interviews, and documentation analysis of lesson plans and student assessment records. The findings indicate that individual needs assessment was systematically integrated into the modification of learning objectives, adaptation of teaching methods and media, classroom organization, and the implementation of adaptive evaluation using performance rubrics and portfolios. The applied strategies included breaking down competency indicators into operational steps, utilizing visual media and step-by-step demonstrations, organizing small structured learning groups, and providing continuous formative feedback. The implementation of these strategies significantly improved students’ participation, independence, and self-confidence in vocational learning activities. The study concludes that learning management based on individual needs assessment is an effective approach to strengthening inclusive education practices in vocational secondary schools.